Imprinting and Promoter Usage of Insulin-Like Growth Factor II in Twin Discordant Placenta - Yan-Min Luo; Qun Fang; Hui-Juan Shi; Lin-Huan Huang; Run-Cai Liang; Guang-Lun Zhuang (Obstetrics and Gynecology International)
Case reports from infant twins suggest that abnormal genomic imprinting may be one of the important causes of twin discordance, but it is unknown whether abnormal genomic imprinting occurs in the placenta. Therefore, we sought to determine the relationship between the imprinting of insulin-like growth factor II (IGF-II) in placenta and twin discordance. We analyzed the imprinting and promoter usage of IGF-II in placenta of normal twins (T0 group), weight discordance (T1 group), and phenotype discordance (T2 group). We found the incidence of loss of imprinting (LOI) for IGF-II was higher in the T2 group than that in the T0 and T1 groups, while there was no difference between T0 and T1 groups. The transcripts of promoter 3 were lower in the T2 group than in the T0 and T1 groups, and lower in the twin placenta with LOI than in those with normal imprinting. Our findings indicate that the promoter 3 specific LOI of the IGF-II gene may be closely related with phenotype discordance, not weight discordance.